Successful Management of Cystitis in a Male Dog - , Payel Kar, J.B. Rajesh, Chethan G.E, Suvendu Kumar Behera, Kalyan Sarma, Hridayesh Prasad (Archives of Current Research International, 2024)
A 5-year-old male mixed breed dog was brought with complaints of fever, vomiting, inappetence, hematuria for 1 week, dysuria, pollakiuria, pain during urination and pain on palpation in the caudal part of abdomen. Haemato-biochemical analysis showed Hemoglobin 9.1 gm/dL, RBC 4.4 million/µL, WBC 24.75 x 103 /µL, and Neutrophil 85%. Urine culture revealed Staphylococci. In USG, urinary bladder wall was markedly thickened and bladder endothelium lining was highly uneven. In urinalysis report, sanguineous color of urine with pH 7.8 and red blood cell (10 cells/HPF) were there. The management of cystitis was done with fluid therapy, broad-spectrum antibiotic, and supportive therapy for a duration one week. The condition of the dog improved and medicines were continued orally for another 2 weeks.